2012
DOI: 10.1002/glia.22329
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐α mediates estrogen‐induced upregulation of glutamate transporter GLT‐1 in rat primary astrocytes

Abstract: Glutamate transporter-1 (GLT-1) plays a central role in preventing excitotoxicity by removing excess glutamate from the synaptic clefts. 17β-estradiol (E2) and tamoxifen (TX), a selective estrogen receptor modulator (SERM), afford neuroprotection in a range of experimental models. However, the mechanisms that mediate E2 and TX neuroprotection have yet to be elucidated. We tested the hypothesis that E2 and TX enhance GLT-1 function by increasing transforming growth factor (TGF)-α expression and thus, attenuate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 54 publications
6
62
1
Order By: Relevance
“…1B) and TGF-␣ mRNA (Fig. 1C) levels, showing a significant increase within 4 h of incubation, in agreement with our previous findings (26). Analogous to the TX-induced GLT-1 protein increase, GLT-1 mRNA was also continuously increased up to 6 days post-treatment (data not shown).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1B) and TGF-␣ mRNA (Fig. 1C) levels, showing a significant increase within 4 h of incubation, in agreement with our previous findings (26). Analogous to the TX-induced GLT-1 protein increase, GLT-1 mRNA was also continuously increased up to 6 days post-treatment (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…We have shown previously that TX enhanced expression of GLT-1 mRNA and protein in astrocytes that was mediated by TGF-␣ (26). Given the mediating role of TGF-␣ in TX-induced GLT-1 expression, we observed that TX increased GLT-1 mRNA levels before the TGF-␣ mRNA increase (30 min versus 1 h).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…1C 1 ). Our earlier studies established that Mn reduced glutamate uptake by decreasing GLAST and GLT-1 mRNA and protein levels (13,23,24). Herein, we corroborated the Mn-induced decrease in astrocytic EAAT2 promoter activity in a time-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 85%